Pengaruh Kualitas Pelayanan Terhadap Word Of Mouth Melalui Kepuasan Mahasiswa Fakultas Syariah Institut Agama Islam Nasional Laa Roiba - Rio Kartika; Sholikul Hadi; Fika Lestari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Quality service in higher education is an important factor in service excellence. Quality service to students will provide satisfaction so as to create Word Of Mouth. Research using quantitative methods with a descriptive approach. The sample was 30 respondents with simple random sampling technique. The data analysis technique uses path analysis. The results show that service quality has a significant effect on Word Of Mouth by 63.4%. Service quality has a significant effect on student satisfaction, amounting to 57.8%. Service quality has a direct effect on Word Of Mouth of 57.7%, an indirect effect of 23.9%, so that the direct effect of service quality on Word Of Mouth is greater than the indirect effect.